Suppressing the endocrine and autonomic stress systems does not impact the emotional stress experience after psychosocial stress. (April 2017) - Ali, Nida; Nitschke, Jonas P.; Cooperman, Cory; Pruessner, Jens C.
Highlights: Pharmacological blockade of stress systems suppressed HPA and ANS response to stress. In contrast the emotional stress experience remained entirely intact. Results indicate dissociation between physiological and emotional stress systems. Results raise questions about contributions of physiological responses in emotional stress. Abstract: Acute psychosocial stress activates the physiological and endocrine stress systems and increases the subjective emotional experience of stress. While considerable efforts have been made to link changes in the activity of the biological stress systems with changes in the subjective emotional experience of stress, results so far have been mixed, at best. To investigate this association in a study employing experimental manipulation, we pharmacologically suppressed both the autonomic and the endocrine stress responses, and investigated the effects of acute psychosocial stress on the emotional stress experience. 22 healthy men and women received dexamethasone (2 mg) the day before, and propranolol (80 mg) one hour before psychosocial stress induction. A control group (n = 24) received placebo pills on each occasion. Salivary cortisol, alpha-amylase and heart-rate responses to stress were assessed before, during and after stress induction. Subjective stress, mood, and state self-esteem assessments were made before and after stress. In the pharmacological manipulation group, subjects demonstrated no increase in autonomic or endocrine stress response, after exposure to psychosocial stress. Despite these effects, the emotional stress experience was intact in this group and identical to the control group. Participants in the experimental group showed an increase in subjective stress, greater mood dysregulation, and lower state self-esteem following stress exposure, with the response magnitude comparable to the control group. Our findings suggest that at least acutely, the physiological stress arousal systems and the emotional experience of stress are dissociated. This raises important questions about the efficacy of our measurement of subjective stress, and the unique contributions of the autonomic and endocrine responses in the subjective stress experience.